2022
DOI: 10.1007/s11356-022-18930-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical analysis of the environmental impacts of fishery complementary photovoltaic power plant

Abstract: Photovoltaic (PV) power plants have shown rapid development in the renewable sector, but the research areas have mainly included land installations, and the study of fishery complementary photovoltaic (FPV) power plants has been comparatively less. Moreover, the mechanism of local microclimate changes caused by FPV panels has not been reported. This work revealed this mechanism using a physical model to illustrate the impact of FPV power plants in a lake on the environment. The results indicated that the lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The average SAT in the PV area is 0.6 • C higher compared to the control area of the case study, while the average water temperature is 1.5 • C lower compared to the control area. The results in our case study are consistent with those of Li et al [19]. They monitored air temperature and water temperature simultaneously and showed that the average air temperature at the PV site is 0.16 • C higher compared to that outside the PV site, and the water temperature is almost lower compared to that outside the PV site.…”
Section: Effects Of Pv On Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…The average SAT in the PV area is 0.6 • C higher compared to the control area of the case study, while the average water temperature is 1.5 • C lower compared to the control area. The results in our case study are consistent with those of Li et al [19]. They monitored air temperature and water temperature simultaneously and showed that the average air temperature at the PV site is 0.16 • C higher compared to that outside the PV site, and the water temperature is almost lower compared to that outside the PV site.…”
Section: Effects Of Pv On Temperaturesupporting
confidence: 92%
“…The coverage of PV power decreases the shortwave radiation within the PV area, which is conducive to a decrease in water and air temperature [20]. On the other hand, it should be noted that the PV panels emit long-wave radiation, thereby contributing to the heating of the surrounding atmosphere [19,21]. The average net shortwave radiation in the PV area (26 W/m 2 ) decreased by 96% compared with that in the control area (717 W/m 2 ) of the case study, while the net longwave radiation increased from −102 W/m 2 in the control area to 44 W/m 2 .…”
Section: Effects Of Pv On Temperaturementioning
confidence: 99%
“…The daily variation of USR for the FPV site is greater than the REF site because the albedo (albedo = USR/DSR) was increased (the FPV site albedo was 6.56%, the REF site albedo was 6.63%) on sunny day. But Li et al found that the albedo is decreased after deploying the PV arrays on lake 20 . Because the albedo of lake is higher than the PV panel materials.…”
Section: Resultsmentioning
confidence: 99%